Approaches to Improve the Bioleaching of Arsenopyrite Flotation Concentrate with Acidithiobacillus ferrooxidans: A Comparison of Two Strains of Different Origin - Tatiana Abashina; Alyona Yachkula; Artem Shaikin; Mikhail Vainshtein (Engineering Proceedings, 2024)
Bacterial leaching is a well-known green technology proposed for the extraction of valuable metals into solution. However, this biotechnology has some “bottle neck” problems too. Arsenopyrite, a gold-bearing ore, is a refractory mineral material that is hardly soluble and contains toxic arsenic compounds which decrease any bioleaching production. The most common biotechnology used for this process is provided with the species Acidithiobacillus ferrooxidans: autotrophic and acidophilic bacterial strains including ones resistant to inorganic arsenic compounds. Common attempts to dissolve arsenopyrite with increasing volumes of sulfuric acid provoke acidification of the environment and its pollution with toxic compounds. In our research, we compared two A. ferrooxidans strains of different origin: TFBk isolated from arsenopyrite ore (pre-adopted to arsenic), the Republic of Kazakhstan, and ShA-GNK isolated from silicate nickel-ferrous ore (laterite, without arsenic), the Russian Federation. The studied genomes of both strains showed the presence of the same genes providing defense against arsenic compounds, but the resistance to toxic compounds was higher in the strain that had never been exposed to any high As concentration under the natural conditions. Both strains showed a weak oxidation of the arsenopyrite flotation concentrate (AFC). In accordance with the published data, supplementation of the medium with formate stimulated bacterial growth in the culturing medium. However, this supplementation to the leaching solution decreased the arsenopyrite oxidation during the first stage of the AFC leaching because formate was used as an alternative energy substrate, but subsequently gave a higher iron yield later.